2022
DOI: 10.1111/nph.17987
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana CYCLIC NUCLEOTIDE‐GATED CHANNEL2 mediates extracellular ATP signal transduction in root epidermis

Abstract: Damage can be signalled by extracellular ATP (eATP) using plasma membrane (PM) receptors to effect cytosolic free calcium ion ([Ca 2+ ] cyt ) increase as a second messenger. The downstream PM Ca 2+ channels remain enigmatic. Here, the Arabidopsis thaliana Ca 2+ channel subunit CYCLIC NUCLEOTIDE-GATED CHANNEL2 (CNGC2) was identified as a critical component linking eATP receptors to downstream [Ca 2+ ] cyt signalling in roots.Extracellular ATP-induced changes in single epidermal cell PM voltage and conductance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…As induced above, the potential biological effects or functions of exATP can be revealed by exogenous application of ATP [ 7 , 13 ]. For example, the elevation of cytosolic free calcium ([Ca 2+ ] cyt ) level is usually used as the indicator of the exATP-induced response [ 46 ]. Tanaka et al [ 47 ] revealed that the concentrations of exogenous ATP as higher as 100 μM can trigger the elevation of [Ca 2+ ] cyt level in Arabidopsis seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…As induced above, the potential biological effects or functions of exATP can be revealed by exogenous application of ATP [ 7 , 13 ]. For example, the elevation of cytosolic free calcium ([Ca 2+ ] cyt ) level is usually used as the indicator of the exATP-induced response [ 46 ]. Tanaka et al [ 47 ] revealed that the concentrations of exogenous ATP as higher as 100 μM can trigger the elevation of [Ca 2+ ] cyt level in Arabidopsis seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…CNGC14 has been tested in Pi-replete conditions and found not to be involved (Shih et al 2015). However, CNGC2, CNGC4 and CNGC6 have since been shown to contribute to the root eATP-induced [Ca 2+ ] cyt elevation in Pi-replete conditions (Duong et al 2022;Wang et al 2022). Among the Glutamate Receptor-Like family (GLR), GLR3.3 and GLR3.6 are involved in leaf wounding and signal propagation (Vincent et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another CNGC, CNGC6, may also be involved in the root’s response ( Duong et al., 2022 ). CNGC2 is also part of the eATP pathway in cotyledons and pollen grain ( Sun et al., 2021 ; Wu et al., 2021 ), although its involvement in roots appears restricted to the epidermis ( Wang et al., 2022a ). CNGC2 may form a connection with PAMP-triggered immunity as it can also operate in flg22 signalling ( Tian et al., 2019 ) and it also works in Jasmonic Acid signalling ( Lu et al., 2016 ).…”
Section: Eatp Signalling Intersects With Multiple Pathwaysmentioning
confidence: 99%